Pembuatan Plang Nama jalan: Pembuatan Papan Petunjuk Jalan Gang di Desa Cikuya RW/04 - maulana, irham Maulana; Al-Dicky, Dhio Muhammad; Millenianda, Hendry (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
This program aims to improve public facilities in Cikuya Village RW04 by installing alley street signs. The absence of street signs often makes it difficult for both local residents and visitors to find specific locations in the village. Through this program, several alley street signs have been installed at strategic points to facilitate accessibility and navigation in the area. The implementation method includes location surveys, sign design, and installation. The outcome of this program is expected to enhance the comfort, safety, and mobility efficiency in Cikuya Village RW04.